IMPLEMENTATION OF SERVICE OF SEQUENCE WAITERS AT LAVENDER RSETAURANT ANGKASA GARDEN HOTEL PEKANBARU - Deli Novianti; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The scriptwriter entitled “Implementation of Service Of Sequence (SOS) Waiters at Lavender Restaurant Angkasa Garden Hotel Pekanbaru” examines the implementation of Service Of Sequence and wants to know about how the obstacles and efforts of the parties management to improve the performance of waiters so that waiters work in accordance with the Service Of Sequence (SOS) at Lavender Restaurant Angkasa Garden Hotel Pekanbaru. The method used in this study is a qualitative method. Where in this study found management efforts to improve the performance of waiters at Lavender Restaurant. The level of succes achieved by the Food and Beverage Service team so far is in the satisfactory category. This is due to the function of the waiters who always follow the Standart Operational Procedure (SOP) or Service Of Sequence (SOS) and creat a good relationship between the functions of the Food and Beverage team and the Food and Beverage team as the front liner. Good and optimal performance of waiters in all respects in terms of health, soft skills and knowledge can increase sales through upselling. Lavender Restaurant Angkasa Garden Hotel Pekanbaru waiters must be able to sell products and communicate wit the guests as well as carry out Standart Operational Procedure or Service Of Sequence. In addition, it requires an active, creative and innovative spirit from waiters. This is necessary to create programs that can be followed to increase restaurant sales. Keywords: Lavender Restaurant, Service Of Sequence, Angkasa Garden Hotel